2014
DOI: 10.1007/s10897-013-9684-1
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing is the Impetus for the Next Generation of Laboratory‐Based Genetic Counselors

Abstract: Next generation sequencing (NGS) is dramatically increasing the number of clinically available genetic tests and thus the number of patients in which such testing may be indicated. The complex nature and volume of the reported results requires professional interpretation of the testing in order to translate and synthesize the meaning and potential benefit to patients, and genetic counselors are uniquely suited to provide this service. The increased need for genetic counselors in this role, coupled with the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…Prenatal genetic counseling is rarely considered a reimbursable expense under third-party payers, meaning that the number of practices that can afford to support prenatal counseling services will remain limited. While some testing companies offer telephone counseling services as part of their business model, it is far from clear that this will be sufficient to address the rising need and there are concerns about conflicts of interest (29,30). For the most part, physicians or other care providers who order these tests will have to counsel patients themselves (31).…”
Section: Counseling and Consentmentioning
confidence: 99%
“…Prenatal genetic counseling is rarely considered a reimbursable expense under third-party payers, meaning that the number of practices that can afford to support prenatal counseling services will remain limited. While some testing companies offer telephone counseling services as part of their business model, it is far from clear that this will be sufficient to address the rising need and there are concerns about conflicts of interest (29,30). For the most part, physicians or other care providers who order these tests will have to counsel patients themselves (31).…”
Section: Counseling and Consentmentioning
confidence: 99%
“…It is not surprising then, that increasing numbers of genetic counselors have been hired to work in a variety of non-genetic clinical settings with non-geneticist physicians (Andermann and Narod 2002;Ingles et al 2011;Matloff and Barnett 2011;Mendes et al 2011;Powell et al 2010;Somers et al 2014;Swanson et al 2014;Vanstone et al 2012). A recent Canadian Association of Genetic Counseling professional status survey revealed that 15 % of respondents work with non-geneticist physicians or with no physicians (CAGC 2012a).…”
Section: Changing Trends In Canadian Healthcare and Genomic Medicinementioning
confidence: 99%
“…The pressure on primary care providers and non-genetics specialists to expand their role in genetic risk assessment and counseling is increasing, despite insufficient training and education (Andermann and Blancquaert 2010;Bensend et al 2014;Carroll et al 2009;Egalite et al 2014;Houwink et al 2012;Korf et al 2014;Mendes et al 2011;Shields et al 2008;Vanstone et al 2012;Zhou et al 2014). It is not surprising then, that increasing numbers of genetic counselors have been hired to work in a variety of non-genetic clinical settings with non-geneticist physicians (Andermann and Narod 2002;Ingles et al 2011;Matloff and Barnett 2011;Mendes et al 2011;Powell et al 2010;Somers et al 2014;Swanson et al 2014;Vanstone et al 2012). A recent Canadian Association of Genetic Counseling professional status survey revealed that 15 % of respondents work with non-geneticist physicians or with no physicians (CAGC 2012a).…”
Section: Changing Trends In Canadian Healthcare and Genomic Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…At the profession-wide level, documentation of the employment status of genetic counselors through the annual status survey should include not only “work setting,” as it now does (http://www.nsgc.org/page/whoaregeneticcounselors), but also the source of employment—in order to reflect the increasing numbers of laboratory-employed genetic counselors who provide direct patient counseling outside of laboratories. This distinction has already been recognized by some insurers, which mandate (and reimburse) genetic counseling only by a non-laboratory-employed genetic counselor for certain covered genetic tests (11). Insurance coverage for genetic counseling may play an increasing role in the employment options of certified genetic counselors, as genetic information is increasingly integrated into clinical care.…”
mentioning
confidence: 99%